2018
DOI: 10.1590/1678-98652018000300003
|View full text |Cite
|
Sign up to set email alerts
|

Birth weight, physical growth and body composition in children: A longitudinal study

Abstract: Objective To describe children’s physical growth (body mass and height) velocity and body composition (fat percentage and Fat Free Mass); to investigate the magnitude of interindividual differences according to age, gender and birth weight categories, as well as to examine the differences in the average trajectories of children with Low Birth Weight and Normal Weight according to international references. Methods The sample consisted of 534 children (279 boys and 255 girls, 7 to 10 years old) evaluated in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 24 publications
(40 reference statements)
3
10
0
Order By: Relevance
“…In this context, Ayyavoo et al (2014), also reported sex‐related differences in the effect of body composition programming, reporting more body fat, less fat‐free mass, and greater abdominal adiposity in girls compared to boys. This demonstrates, in a way, a degree of heterogeneity, mainly concerning body composition, which can be explained by differences in the rate at which child growth occurs in this age range (dos Santos et al, 2018).…”
Section: Discussionmentioning
confidence: 95%
See 4 more Smart Citations
“…In this context, Ayyavoo et al (2014), also reported sex‐related differences in the effect of body composition programming, reporting more body fat, less fat‐free mass, and greater abdominal adiposity in girls compared to boys. This demonstrates, in a way, a degree of heterogeneity, mainly concerning body composition, which can be explained by differences in the rate at which child growth occurs in this age range (dos Santos et al, 2018).…”
Section: Discussionmentioning
confidence: 95%
“…A previous study, although with a cross‐sectional design, showed that children with LBW were lighter and smaller than their peers, with reduced indices for weight‐for‐age and height‐for‐age (Tchamo et al, 2017). In another study with a longitudinal design developed by dos Santos et al (2018), it was observed that LBW alone does not appear to be a sensitive marker of dynamic changes in the trajectories of physical growth and body composition of children from 7 to 10 years of age. However, studies have reported the existence of significant relationships between birth weight and weight gain in childhood, especially in fat‐free mass, % BF, and body fat distribution, although there are no implications for gains in height (Okosun et al, 2000; Walker et al, 2002; Wells, 2017; Wells et al, 2005).…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations